PELATIHAN PEMANFAATAN CANVA SEBAGAI MEDIA KREATIF UNTUK MENINGKATKAN KOMPETENSI DESAIN SANTRI DI PONDOK PESANTREN AN-NAWAWI 2 SALAMAN - Marista Putri Ariftina; Laili Syarifah (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2026)
Canva training was conducted during community service at the An-Nawawi 2 Magelang Islamic boarding school. The purpose of this community service is to explain how to enhance creativity by utilizing the Canva application as a means of development and progress for the boarding school. Through this training, participants will be trained to create attractive professional promotional materials, such as posters, brochures, leaflets, and social media content, with the aim of improving the image and expanding the reach of the boarding school's da'wah. Additionally, this training allows the boarding school to remain independent and build its own visual identity, such as by creating logos for various business units. This will enable the boarding school to increase its branding value and business appeal. It is expected that the use of the Canva application will accelerate the process of enhancing the creativity of the students, and make the pesantren (Islamic boarding school) more prepared to keep up with technological advancements, thereby expanding the role of da'wah and strengthening the economic independence of the pesantren. This study uses the ABCD (Asset Based Community Development) method. This method is intended so that the students can better utilize modern digitalization for the progress of the pesantren. The subjects of this community service are the students. The results of this service show that in the Discovery method, digital design knowledge is still low. In the Dream method, it was found that students and pesantren administrators hope that the pesantren can be better known to the outside community. In the Design method, strategic initiatives were designed to advance the students' creative thinking by conducting small-scale socialization on the basic knowledge of using Canva. In the Design method, the strategic initiative is created to advance the creative thinking of the students by conducting a small-scale socialization on basic knowledge of using Canva. In the Define method, Canva training focuses on enhancing the abilities of students and student administrators to create promotional designs, dakwah content, and pesantren business logos. Besides developing the image, it can also be used for digital dakwah and the economic independence of the pesantren. In the Destiny/Delivery method, researchers implement all the plans that have been made by collaborating with administrators and students to ensure that this Canva socialization can become an engaging and comfortable way to expand the reach of promotions as well as channel students' creativity through the Appreciative Inquiry approach (Discovery, Dream, Define, Destiny).